2015
DOI: 10.1007/s12098-014-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Clinical Profile of Hospitalized Children with Moderate and Severe Acute Malnutrition in South India

Abstract: Though 11.5 cm MUAC has been mentioned by WHO as the cut off for identifying SAM, a higher cut off (12 cm) may be required to use it as a screening tool. Mothers' education, pre-lacteal feeds and co-morbidities were found to be independent determinants for malnutrition in the present patient population, indicating the need towards a targeted approach for modifying these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 19 publications
0
19
3
2
Order By: Relevance
“…Moderate anaemia: 7-9.9 g/dL 3. Severe anaemia: <7 g/dL Leukopenia and thrombocytopenia was defi ned according to the normal values for the age of the child 5 . Based on above methodology and defi nitions both cases and controls were classifi ed and mean values of various haematological indices were studied.…”
Section: Morphologic Classifi Cation Of Anaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate anaemia: 7-9.9 g/dL 3. Severe anaemia: <7 g/dL Leukopenia and thrombocytopenia was defi ned according to the normal values for the age of the child 5 . Based on above methodology and defi nitions both cases and controls were classifi ed and mean values of various haematological indices were studied.…”
Section: Morphologic Classifi Cation Of Anaemiamentioning
confidence: 99%
“…Severe anaemia is a leading cause of paediatric morbidity, hospitalization, and mortality and it is very important co morbidity in children with severe acute malnutrition 3,4,5,6,7 . Severe Acute Malnutrition (SAM) with anaemia has been shown to have higher mortality as compared to SAM with no anaemia 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported on morbidity in children with moderate wasting or moderate acute malnutrition (MAM) [9][10][11][12][13][14][15] and most based only on symptom-recall. Current case definitions of MAM includes children with moderate wasting and/or a mid-upper arm circumference (MUAC) between 115 and 125 mm [16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequentemente, tais fatos podem influenciar no aumento da taxa de mortalidade nesta faixa etária (Devi et al, 2015;Chisti et al, 2014;Moreno et al, 2016).…”
Section: Discussionunclassified
“…Neste sentido, avaliamos a condição nutricional dos pacientes na admissão, e analisando o cálculo do Z escore estatura/idade, foi evidenciado uma baixa estatura para a idade, demonstrando acometimento nutricional crônico predominante, com retardo do crescimento linear (Isaac et al, 2012;Montejo et al, 2010;Martins et al, 2009 (Atalah et al, 2012). No entanto, resultados diferentes foram encontrados em uma análise realizada com crianças asiáticas por Devi et al (2015) e Fivez et al (2016), que ao avaliarem o Z escore peso/estatura, evidenciaram a condição nutricional classificada como magreza acentuada na população estudada, indicando acúmulo insuficiente de massa corporal ou catabolismo de tecidos corporais e, portanto situações de depleção nutricional aguda. Tal fato; e de grande relevância, já que a avaliação do peso/estatura significa a harmonia entre as dimensões de massa corporal e altura (Isaac et al, 2012;Montejo et al 2010;Martins et al, 2009;Atalah et a., 2012).…”
Section: Discussionunclassified